Temporomandibular joint disk adhesion: evidence from magnetic resonance images - MELO,Daniela Pita de (2014)
This case report has the aim to present an adhesion of the temporomadibular disc to the articular eminence, diagnosed on magnetic resonance imaging images. A 37-year-old female patient with TMJ (temporomandibular joint) disk adhesion on the left side and complaining of bilateral otalgia over the last 2 years is reported in the present article. The patient did not complain of articular pain or clicking, or any other noises of any nature. Clinical observation showed that the patient had restricted jaw opening, with mandibular deviation the left side without correction during mandibular movement. Our diagnostic impression was of partial anterior disk displacement with reduction of the right side disc; and partial anterior disk displacement with reduction and disc disk adhesion with hypo-mobility of the condyle, on the left temporomandibular joint. The peculiarity of this reported case is the fact that besides the bilateral partial anterior disc displacement, there was also found an adhesion of the disc on the left side. In conclusion, the magnetic resonance imaging exam of the temporomandibular joint can be considered an exam of choice for the evaluation of disc positioning and its morphological alterations.